Program Bidang Bimbingan dan Konseling untuk Pengembangan Kepribadian Siswa di Madrasah Aliyah Negeri 2 Pekanbaru - Fatimah Fatimah; Amirah Diniaty (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2023)
This research aimed at knowing Guidance and Counseling program for personality development of Muslim students, students' personalities developed in Guidance and Counseling program, and Qualitative approach was used in this research, and the participants of this research were 2 Guidance and Counseling teachers at State Islamic Senior High School 2 Pekanbaru and 2 students who were chosen by the Guidance and Counseling teachers because they had received Guidance and Counseling services directly during their study period. The data were collected by using observation, interview, and documentation techniques. The data obtained from the results of interview and observation were reduced, displayed and concluded. The research findings showed that:Guidance and Counseling program for personality development of Muslim students at school was found in all fields-personal guidance, social, learning, career, religious life, and family life, but the fields of career and learning guidance were more focused with the help of psychological test assessments for students at the beginning of the new Academic Year when they first entered State Islamic Senior High School 2 Pekanbaru; students become personals who were adaptable, responsible, respectful, appreciative, competitive, and ambitious.